Are Psycho-Behavioral Factors Accounting for Longevity? - Fernández-Ballesteros, Rocío; Sánchez-Izquierdo, Macarena (Frontiers in Psychology, 2019)
The general objective of this article is to critically review the state of the art regarding current factors accounting for aging, longevity and successful longevity. There are two major constructs which most authors are employing to account for longevity: genetic or intrinsic components versus environmental or extrinsic factors. This classification has important flaws: i) From an epigenetic standpoint, such a polar classification could lead to misconceptions since both factors are interdependent through lifelong interactions. ii) There are no specifications regarding these “environmental” factors, which include a broad heterogeneity of conditions (physical, economic, social and cultural aspects as well as behavioural ones such as lifestyles) but do not include personal conditions, such as psychological characteristics. The review of the new paradigm called successful aging yields an important set of psycho-behavioural factors, and although population indexes such as Disability Free Life Expectancy (DFLE) or Healthy Life expectancy (HLE) have been developed, authors do not take into consideration healthy or successful longevity as a potential prolongation of the new paradigm of active or successful aging. There is a broad corpus of research literature supporting the importance of psycho-behavioural (PB) factors intervening in the ways of aging, specifically intelligence and cognitive functioning, positive emotion and control, personality traits, psychosocial, physical conditions and lifestyles, all of which are highly associated with active aging, health, longevity and survival. The importance of these factors accounting for longevity, and successful longevity must be taken into consideration as a pending issue in gerontology.